The Use of Gravitational Lenses in the Study of Distant Galaxy Mergers - Kats, A.V.; Kontorovich, V.M. (Радиофизика и радиоастрономия, 2013)
The paper is based on the report at the conference EMES-2012 dedicated to P. V. Bliokh, one of the pioneers in the study of gravitational lenses. We discuss a vivid example of observation of the galaxy merger at a redshift close to z= 3 using gravitational lensing (by Boris, et al. and Berciano Alba, et al.). In connection with observation of the galaxy luminosity function evolution in the Hubble ultra deep field (Bouwence, et al.), a description of the mass function slope evolution due to minor mergers is proposed, which satisfactorily describes the results of observations. В статье, написанной по материалам доклада на конференции EMES-2012, посвященной одному из пионеров исследования гравитационных линз П. В. Блиоху, приводится яркий пример наблюдения (Борис и др., Берсиано Альба и др.) слияний галактик при красном смещении, близком к z = 3, с использованием гравитационного линзирования. В связи с наблюдениями эволюции функции светимости галактик (Боуенс и др.) в сверхглубоком поле Хаббла предлагается модель эволюции наклона функции масс за счет малых слияний, удовлетворительно описывающая результаты наблюдений. У статті, написаній за матеріалами доповіді на конференції EMES-2012, присвяченої одному з піонерів дослідження гравітаційних лінз П. В. Бліоху, наведено яскравий приклад спостереження (Борис та ін., Берсіано Альба та ін.) злиттів галактик при червоному зсуві, близькому до z = 3, з використанням гравітаційного лінзування. У зв'язку із спостереженнями еволюції функції світності галактик (Боуенс та ін.) у надглибокому полі Хаббла запропононовано модель еволюції нахилу функції мас за рахунок малих злиттів, що задовільно описує результати спостережень.